2015
DOI: 10.1109/tim.2015.2390833
|View full text |Cite
|
Sign up to set email alerts
|

Parametric System Identification Using Quantized Data

Abstract: The estimation of signal parameters using quantized data is a recurrent problem in electrical engineering. As an example, this includes the estimation of a noisy constant value, and of the parameters of a sinewave that is its amplitude, initial record phase and offset. Conventional algorithms, such as the arithmetic mean, in the case of the estimation of a constant, are known not to be optimal in the presence of quantization errors. They provide biased estimates if particular conditions regarding the quantizat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…The variance of each component of Y can be approximated using a Taylor series expansion of −1 (p h ) about the mean value ofp h . In [19], it is shown that this calculation provides…”
Section: ) Partitioning the Input Samplesmentioning
confidence: 94%
See 4 more Smart Citations
“…The variance of each component of Y can be approximated using a Taylor series expansion of −1 (p h ) about the mean value ofp h . In [19], it is shown that this calculation provides…”
Section: ) Partitioning the Input Samplesmentioning
confidence: 94%
“…Previous research on this subject considered the estimation of systems parameters when the input sequence is known [17], [18] and when the input signal is synchronously sampled, that is, when the ratio between the sampling sequence period and the signal period is a rational number [19]. Several other papers have addressed a wide class of similar problems in the context of system identification [20]- [27].…”
Section: State Of the Artmentioning
confidence: 99%
See 3 more Smart Citations